In vitro pharmacokinetics/pharmacodynamics of FL058 (a novel beta-lactamase inhibitor) combined with meropenem against carbapenemase-producing Enterobacterales - Huang, Zhiwei; Bian, Xingchen; Li, Yi; Hu, Jiali; Guo, Beining; Yang, Xinyi; Jin, Yi; Zheng, Shansong; Wang, Xinmei; Gao, Cong; Zhang, Jing; Wu, Xiaojie (Frontiers in Pharmacology, 2024)
Objective: FL058 is a novel beta-lactamase inhibitor with a broad-spectrum of activity and a favourable safety profile. The objective of this study was to evaluate pharmacokinetic/pharmacodynamic (PK/PD) relationships for the combination of FL058 and meropenem in an in vitro infection model. Methods: By simulating human concentration-time profiles in the in vitro model, meropenem in combination with FL058 when administered 1 g/0.5 g, 1 g/1 g, 2 g/1 g and 2 g/2 g q8h by 3-h infusion achieved approximately 2 -4 log10 kill to KPC/OXA-producing Klebsiella pneumoniae and Escherichia coli; the combination therapy could not inhibit NDM-producing K. pneumoniae, but could maintain NDM-producing E. coli around baseline.The PK/PD indexes that best described the bacterial killing from baseline in log10 CFU/ml at 24 h were the percent time of free drug above MIC (%fT> MIC, MIC with FL058 at 4 mg/L) for meropenem and the percent time of free drug above 1 mg/L (%fT> 1 mg/L) for FL058. The targets for achieving a static effect and the 1-and 2-log10 kill were 74, 83, 99 for %fT> MIC of meropenem and 40, 48, 64 for %fT> 1 mg/L of FL058, respectively. The PK/PD index of %fT> 1 mg/L can provide a basis for evaluating clinical dosing regimens for FL058 in combination with meropenem.Conclusions: FL058 in combination with meropenem might be a potential treatment for KPC-and/or OXA-48-producing Enterobacterales infection.